Interactive web-based data visualization with R, plotly, and shiny - Sievert, Carson (Chapman and Hall/CRC the R series, 2020)
"This book describes interactive data visualization using the R package plotly. It focuses on tools and techniques that data analysts should find useful for asking follow-up questions from their data using interactive web graphics. A basic understanding of R is assumed"--